Epidemiology and management of acute coronary syndrome in remote and resource-limited settings: Insights from a rural Indonesian hospital - Afandy, Jonathan E.; Taslim, Taslim; Sari, Yuliyana; Fajarwati, Dinda D.; Tanjung, Benny Y. (Narra J, 2025)
Acute coronary syndrome (ACS) remains a major global health and economic burden. In Indonesia, North Kalimantan reports the highest prevalence of heart disease (2.2%), exceeding the national average of 1.5%. Nunukan, the province’s northernmost and predominantly archipelagic region, is served by a single general hospital, reflecting the healthcare challenges faced by many rural Indonesian areas. This study aimed to provide epidemiological insights into ACS cases in this region to inform improved management strategies in similar resource-limited settings. A retrospective cross-sectional study was conducted among ACS patients admitted to Nunukan Regency General Hospital, Nunukan, Indonesia, between January 1 and August 31, 2023. Data on demographics, risk factors, clinical presentation, vital signs, diagnostic findings, treatments, and outcomes were collected from paper-based medical records. Of the 241 patients admitted, 4.56% were diagnosed with ST-elevation myocardial infarction (STEMI), 35.68% with very high-risk non-ST-elevation ACS (VHR NSTE-ACS), and 59.75% with non-very high-risk NSTE-ACS (NVHR NSTE-ACS). The mean age was 55.4±12.26 years, with a predominance of males (51.5%) and obesity (35.7%). The median number of risk factors was 2 (IQR: 1–2.5), with hypertension being the most prevalent (72.6%). Late presentation was common, and only 36.4% of STEMI patients received fibrinolytic therapy. The overall in-hospital mortality rate was 3.3%, and the median length of stay was 6 days (IQR: 5–7). ACS patients in Nunukan exhibited distinct clinical and demographic profiles, characterized by younger age, obesity, multiple risk factors, and delayed presentation. These findings highlight the urgent need to strengthen cardiovascular care capacity and early intervention strategies in remote and resource-limited regions of Indonesia.